"Pooling our resources": Equalization and the origins of regional universality, 1937–1957. (September 2014) - Bryden, P.E.
Abstract This paper places Canada's equalization program in the context of broader discussions of equality and universality that dominated the mid‐twentieth century discourse. It examines the origins of equalization in the Rowell‐Sirois Report, the flirtation with equalization during the Dominion‐Provincial Conference on Reconstruction in 1945–46, and the intergovernmental discussions of the 1950s that led to the first formal implementation of equalization in 1957. It argues that a system of universal regional equalization grants arose not only because of the lessons of the Depression and the regional inequalities surfacing during the 1930s, but also as a by‐product of the move to universal social security measures, such as family allowances and, later, health insurance.